Utilization of Vacuum Frying Technology for Horticultural Postharvest Processing in Banyuwangi Farmer Groups - Susilo, Bambang (Journal of Innovation and Applied Technology, 2025)
Sumber Kencono Village in Banyuwangi is known for its horticulture, such as shallots and fruits. However, farmers face challenges in processing and marketing their crops. The Doktor Mengabdi program introduced vacuum frying technology to enhance product value and shelf life by processing shallots and fruits into high-quality chips. The program involved technology introduction, processing training, questionnaires, and Business Model Canvas (BMC) socialization for the Sumber Beras Farmer Group. Results showed that 95% of participants improved their understanding of vacuum frying. This technology effectively boosts product selling value and longevity. Satisfaction evaluations indicated that most participants were pleased with the program. The BMC analysis revealed that chip products have significant market potential. Implementing this technology is expected to increase farmer group incomes and improve the welfare of Sumber Kencono Village.